PROPHETIC CRITICISM OF TEMPLE RITUALS: A REFLECTION ON MALACHI’S IDEA ABOUT YAHWEH AND ETHICS FOR FAITH COMMUNITIES - Boloje, Blessing Onoriode (Scriptura, 2015)
This article presents some perspectives about Yahweh and ethics from Malachi’s criticism of the rituals of the temple. Malachi’s theological and ethical uniqueness is observed somehow most clearly in the preponderance of negative emphasis the prophetic book places on temple rituals and the way the language of the cult dominates its analysis of malpractices. Prophetic criticism of temple rituals, as this article demonstrates, lies at the heart of the controversy between the prophets and the priest; namely the role of cult and ethics in the religion of Ancient Israel. While scholars have yet to explain fully the phenomenon of criticism of the cult in prophetic writings, this article brings the prophets and the priests closer by proposing that the one way to explain the discrepancy is to advocate that these prophets could not see the importance of rituals for the improvement of ethical life. If the cult is understood to be the vertical dimension of the Law and ethics its horizontal dimension, one would notice that these dimensions go together, both are expressions of God’s will. When the vertical dimension (worship, offering, sacrifice) is experiencing some degree of dysfunction, the horizontal dimension (social justice, etc.) will be affected. Malachi’s emphasis on the temple obviously helps one to see that there was nothing wrong with the cult unless it was not used appropriately and effectively to enhance the ethical life of the people as an essential component of the larger framework of the covenant relationship that Yahweh had with them as his people. The article thus emphasizes some underlying theological reflection on the uniqueness of Malachi’s oracles about Yahweh and ethics for faith communities.